Serum surfactant protein D as a significant biomarker for predicting occurrence, progression, acute exacerbation, and mortality in interstitial lung disease: a systematic review and meta-analysis - He, Xing; Ji, Jiaqi; Zheng, Dan; Luo, Zeli; Luo, Linjie; Guo, Lu (Frontiers in Immunology, 2025)
ObjectiveSerum surfactant protein D (SP-D) is a potential biomarker for the non-invasive prediction of interstitial lung disease (ILD) status. However, previous studies lacked comprehensively qualitative and quantitative pooled analysis methods to summarize the relationship between SP-D and ILD.MethodsWe conducted a comprehensive literature search from PubMed, Embase, Web of Science, Scopus, Ovid, and Cochrane Library, up to 16 December 2023. The Newcastle–Ottawa Quality Assessment Scale was employed to evaluate the quality of each included study. Pooled analyses were primarily performed for weighted mean difference (WMD), odds ratio (OR), and hazard ratio (HR). Sensitivity analysis was conducted by sequentially eliminating one study at a time and reanalyzing the remaining studies. In addition, the trim-and-fill method was applied for correcting publication bias.ResultsMore than 3,561 patients with ILD from 41 articles were included for pooled analysis. The pooled results showed that serum SP-D levels were higher in the ILD group than the control group (WMD = 120.24 ng/mL, 95% CI: 72.45–168.03, p<0.001). Additionally, SP-D levels among patients with ILD were significantly elevated in the acute exacerbation (AE) group compared with the non-AE group (WMD = 9.88 ng/mL, 95% CI: 2.64–17.12, p=0.008), and in the death group compared with the survival group (WMD = 32.98 ng/mL, 95% CI: 2.11–63.84, p=0.036). However, no significant difference was observed between the progression group and the stable group (WMD = 13.54 ng/mL, 95% CI: −23.68–50.76, p=0.227). In addition, pooled results demonstrated that serum SP-D was a reliable predictive factor for various outcomes associated with ILD: occurrence (OR=4.66, 95%CI = 2.46, 8.86, p<0.001), progression (OR=1.003, 95%CI= 1.001, 1.006, p=0.033), and mortality (HR=1.002, 95%CI= 1.001, 1.003, p=0.023) of ILD. In contrast, there was no significant difference for predicting AE (HR = 1.004, 95% CI = 0.997, 1.011, p=0.240).ConclusionSerum SP-D is a significant biomarker associated with ILD occurrence, progression, acute exacerbation, and mortality. It remains essential to clarify the predictive value of serum SP-D levels concerning the disease status in patients with different ILD subtypes. Moreover, it may be beneficial to conduct a combined analysis of SP-D with other potential biomarkers to further enhance its diagnostic capability regarding the disease status in patients with ILD.Systematic Review Registrationhttps://inplasy.com/inplasy-2024-5-0050/, identifier INPLASY 202450050.